MODERN APPROACHES FOR DEVELOPING LANGUAGE SKILLS IN FOREIGN LANGUAGE TEACHING - Farhodova Shahzoda Umid qizi; Toshboeva Malikabonu Abduvali kizi (TADQIQOTLAR, 2026)
Abstract: This article examines modern approaches to developing language skills in foreign language teaching. The study focuses on innovative pedagogical strategies that enhance learners’ listening, speaking, reading, and writing abilities in contemporary educational contexts. Emphasis is placed on communicative, cognitive, and technology-integrated approaches that support learner-centered instruction. The research highlights how modern methodologies contribute to increased learner motivation, autonomy, and communicative competence. The findings demonstrate that the effective integration of modern approaches significantly improves language skill development and overall learning outcomes.